2020
DOI: 10.1136/bmjopen-2019-031768
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect healthcare costs of lung cancer CT screening in Denmark: a registry study

Abstract: IntroductionA study based on the Danish Randomised Controlled Lung Cancer Screening Trial (DLCST) calculated the healthcare costs of lung cancer screening by comparing costs in an intervention group with a control group. Participants in both groups, however, experienced significantly increased negative psychosocial consequences after randomisation. Substantial participation bias has also been documented: The DLCST participants reported fewer negative psychosocial aspects and experienced better living condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 37 publications
0
9
0
3
Order By: Relevance
“…35 This will also increase the costs even more. We have in previous research shown that low-dose CT screening for lung cancer will in a Danish context with a public funded healthcare system increase total health costs by 60% 16 and specifically for those with false-positive results the cost will increase by 66%. 15 The knowledge of psychosocial consequences from false-positive results contributes to the evidence for the benefits and harms of lung cancer CT screening and should be included in the overall assessment of the European trials.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…35 This will also increase the costs even more. We have in previous research shown that low-dose CT screening for lung cancer will in a Danish context with a public funded healthcare system increase total health costs by 60% 16 and specifically for those with false-positive results the cost will increase by 66%. 15 The knowledge of psychosocial consequences from false-positive results contributes to the evidence for the benefits and harms of lung cancer CT screening and should be included in the overall assessment of the European trials.…”
Section: Discussionmentioning
confidence: 96%
“…9 A false-positive screening result can cause both physical and psychosocial harms [10][11][12][13] as well as being costly for the healthcare system. [14][15][16] The average false-positive rate per screening round varies substantially in lung cancer screening trials, for example, 23% in the NLST and 3% in the DLCST (online supplementary appendix 1). 3 17 Qualitative and quantitative studies have shown that false-positive lung cancer screening results can be associated with negative psychosocial consequences both during workup and after the final diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Another study, investigating healthcare use and costs in DLCST participants showed more use of the healthcare system among false-positives and true-positives compared with the control group in the period of time between two screening rounds, which for the false-positives might be valid subtle surrogate outcomes for negative psychosocial consequences [22]. Further, a comprehensive analysis of healthcare costs in DLCST participants showed that the CT group and the control group had significantly increased total healthcare costs, calculated at 60 % and 48 % respectively when they were compared to a random sample of current or former heavy smokers in the general Danish population, who had never been invited to participate in lung cancer screening [23]. This may be associated with the process, described by Andersen and colleagues, where the emphasis on early diagnosis changes the way bodily sensations are interpreted by the public -'what counts as cancer symptoms' is steadily being subdivided, classified and expanded [24].…”
Section: Annual Screening Roundmentioning
confidence: 99%
“…La qualité de vie a été évaluée par DLCST [59,[80][81][82], UKLS [83] ainsi que dans un sous-groupe de NLST [84] et de NELSON [85][86][87]. DLCST rapporte un impact psychosocial négatif au fil des tours de dépistage chez tous les participants mais significativement plus important dans le bras contrôle.…”
Section: Qualité De Vieunclassified